CicloGis: um Sistema Web para a comunidade do ciclismo de Belém do Pará - GOMES, Ruan Ribeiro (2024)
Urban mobility is a persistent challenge in several Brazilian cities. This work presents CicloGis, a web system developed to support the cycling community of Belém do Pará. The objective of CicloGis is to provide detailed information about cycling infrastructure, promote safety and encourage the use of bicycles as a sustainable means of transport. Using WebGIS tools, the system allows access to georeferenced data on cycle paths, cycle lanes and cycling groups. The methodology includes field research, participatory design and the use of open source technologies for web development. The results show that CicloGis is an effective tool in promoting sustainable urban mobility for Brazilian cities.